Price Sensitivity and Switching Intention in Mobile Broadband Services - Sylvia Samuel; Daniel Widjaja; Thomas Green (APTISI Transactions on Management (ATM), 2026)
The rapid growth of digital connectivity has intensified competition in the mobile broadband industry, increasing the importance of understanding factors that influence customer switching behavior. Although prior studies have examined switching intention in telecommunications services, limited research has simultaneously investigated the roles of brand perception, price sensitivity, and service quality while considering demographic heterogeneity. This study examines the effects of brand perception, price sensitivity, and service quality on switching intention in the mobile broadband sector and evaluates the moderating role of gender. A quantitative survey was conducted among 153 mobile broadband users, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that price sensitivity significantly increases switching intention, indicating that consumers who are more responsive to price differences are more likely to change service providers. In contrast, brand perception and service quality do not significantly influence switching intention, suggesting that mobile broadband services are increasingly perceived as technologically homogeneous across providers. Furthermore, gender does not moderate the relationships between the key determinants and switching intention, although it shows a significant direct effect. These findings highlight the dominant role of economic evaluation in switching decisions and provide strategic implications for telecommunications providers in developing competitive pricing and customer retention strategies.